Thermographic inspection method application for the detection of imperfections for steel structures - Kolesnichenko, S.; Popadenko, А. (Ways to Improve Construction Efficiency, 2019)
The article provides the theoretical basis and practical examples of thermographic inspection method for detection of cracks and corrosion damage of steel structures. The authors conclude that thermographic inspection method can be used for inspection of steel structures for the qualitative assessment of the presence of cracks and areas of corrosion damages.